Konsep T̲âghût Dalam Al-Qur’an - Titok Priastomo (Rayah Al-Islam, 2020)
The word t̲âghût has become a key word in the discourse of terrorism. This keeps the word t̲âghût from its position as one of the key words of the Qur'an. This study conducts a semantic analysis of all verses containing the word t̲âghût to get one general concept that can abstract various forms of t̲âghût in the Qur'an. Based on the theory which states that language is formed by a particular worldview so that the key words in that language can reflect the worldview that shapes it, this study analyzes the al-Qur'an's worldview which is reflected by the concept of t̲âghût. This study concludes that the t̲âghût in the Qur'an is a creature who goes beyond his boundary as a servant of Allah by establishing his own authority to regulate humans without relying on God's guidance. Al-Qur'an's worldview is an integral view that places God in a central position. In this theocentric structure, humans are seen as creatures who must submit to God in carrying out their affairs. By uncovering the concept of t̲âghût in the Qur'an and the worldview that it reflects, this study intends to strengthen the position of the word t̲âghût as a key word of the Qur'an that is free from the context of the issue of terrorism.